The Relationship Of Compliance With Posyandu Visits And Accuracy Of MP-ASI Portions With Stunted Incidents In Yosowilangun Village, Manyar District - palupi, finna retno; Ariestiningsih, Eka Srirahayu; Rahma, Amalia (Universitas Muhammadiyah Gresik, 2024)
The prevalence of stunting is still increasing, including in Indonesia. The prevalence of stunting in 2022 in East Java province is 19.2%, while stunting in Gresik Regency in 2022 is 10.7% (Ministry of Health, 2022). However, at the end of 2023 there was a spike in stunting cases in Gresik which caused the percentage of stunted toddlers to rise. The aim of the research was to determine the relationship between compliance with Posyandu visits and accuracy of MP-ASI portions with short incidents (Stunted) in Yosowilangun Village, Manyar District. The research design method used is cross-sectional and the sampling method uses Proportioned Random Sampling. This research population involved mothers who had children aged 6-24 months who were registered at the Yosowilangun Village Posyandu. The sampling technique is Simple Random Sampling. The sample size was 112 toddlers. The results of the bivariate analysis between compliance with posyandu visits and appropriate portions of MP-ASI administration and the incidence of stunting were obtained (p = 0.000). Based on the data above, it can be concluded that compliance with Posyandu visits and the correct portion of MP-ASI delivery are significantly related to the incidence of stunting in Yosowilangun village.